2003
DOI: 10.1016/s1525-0016(03)00037-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of DNA to the mitochondrial compartment via import sequence-conjugated peptide nucleic acid

Abstract: We report that oligonucleotides can be introduced into the mitochondria of living mammalian cells by annealing them to peptide nucleic acids coupled to mitochondrial targeting peptides. These complexes are imported into the mitochondrial matrix through the outer and inner membrane import channels of isolated mitochondria. They are also imported into the mitochondria of cultured cells, provided that the cytosolic uptake of the complexes is facilitated by using synthetic polycations or membrane permeabilizing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 40 publications
3
108
0
Order By: Relevance
“…hanced their delivery to mitochondria (29,37), but that strategy failed in cases of macromolecules and hydrophobic molecules, including mtDNA and mitochondrial proteins (38). Liposomebased carriers can import hybrid molecules into mitochondria of whole cells, but this approach suffers from low efficiency and high cytotoxicity (8,25,39).…”
Section: Discussionmentioning
confidence: 99%
“…hanced their delivery to mitochondria (29,37), but that strategy failed in cases of macromolecules and hydrophobic molecules, including mtDNA and mitochondrial proteins (38). Liposomebased carriers can import hybrid molecules into mitochondria of whole cells, but this approach suffers from low efficiency and high cytotoxicity (8,25,39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the conjugation or direct modification of MTS permitted a macromolecule such as a protein, DNA and a liposomal nanocarrier to be delivered to mitochondria [8][9][10][11][12] . On the other hand, some researchers have reported the use of a mitochondrial RNA aptamer for mitochondrial delivery.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the information about mitochondrial-targeted delivery of nano carrier has been limited, although many mitochondrial deliveries for various molecules have been reported (Mukhopadhyay and Weiner, 2007;Zhang et al, 2011), especially in the case of low molecular weight drugs (D'Souza et al, 2008;James et al, 2007;Wipf et al, 2005). The use of a mitochondrial targeting signal peptide (MTS) makes it possible to selectively deliver a variety of chemicals, proteins and linear DNA to mitochondria (Asayama et al, 2006;Flierl et al, 2003;Schatz, 1996). It is expected that MTS can be a useful ligand for selective mitochondrial delivery of nanoparticle.…”
Section: Introductionmentioning
confidence: 99%